Urgent assessment needed to evaluate potential impacts on cetaceans from deep seabed mining - Thompson, Kirsten F.; Miller, Kathryn A.; Wacker, Jake; Derville, Solène; Laing, Christopher; Santillo, David; Johnston, Paul (Frontiers in Marine Science, 2023)
Deep seabed mining operations, if permitted, could present significant risks to ocean ecosystems. Disturbance on any scale is likely to be long lasting and irreversible. Scant research to date has examined the impact that deep sea minerals extraction would have on cetaceans. The Clarion-Clipperton Zone (CCZ) is of particular interest to mining companies aiming to exploit polymetallic nodules. The CCZ, with an average depth of 5,500 m and an area of approximately 11,650,000 km2, is a habitat for cetaceans including baleen (mysticetes) and toothed whales (odontocetes). Of particular concern is anthropogenic noise. If permitted, commercial-scale mining is expected to operate 24-hours a day, at varying depths. The sounds produced from mining operations, including from remotely operated vehicles on the seafloor, overlap with the frequencies at which cetaceans communicate, which can cause auditory masking and behavior change in marine mammals. Cetaceans are already facing numerous stressors, including climate change, and many species are still recovering from centuries of exploitation. We argue the need for urgent research to assess more fully the potential impact of deep seabed mining on cetaceans.